Perselingkuhan dan Kekerasan terhadap Perempuan dalam Pemberitaan Media iNews.id (Analisis Wacana Kritis Perspektif Sara Mills) - Hatari Marwina Siagian; M. Surip; Syairal Fahmy Dalimunthe (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
The purpose of this study is to examine how women victims of infidelity and violence are constructed through news texts that determine the structure and meaning of the news presented in news stories on violence against women on iNews.id published on Friday, February 26, 2021 and Thursday, April 09, 2020 This research is a qualitative research. Data collection techniques used listening and note-taking techniques with the help of data collection tables. Data analysis was carried out with a description of Sara Mills' perspective analysis to see the position of the subject-object and the position of the writer-reader. Based on the research results, it can be said that from the news of infidelity and violence against women in the iNews.id media coverage, women are constructed as subjects, not as objects of exploitation. However, in its presentation, women are still depicted as marginal, weak, powerless and sensitive women. The media coverage of iNews.id positioned the reader as the subject of ideology. The reader is brought to the position of the narrator (the storyteller) so that the reader accepts it as reality.